Rapid inducible protein displacement in Plasmodium in vivo and in vitro using knocksideways technology [version 1; referees: 3 approved] - Katie R. Hughes; Andy P. Waters (Wellcome Open Research, 2017)
A deeper understanding of the biology of the Plasmodium parasite is essential in order to identify targets for interventions, with the ultimate aim of eliminating malaria. Determining the function(s) of essential proteins in Plasmodium has, until recently, been hampered by the lack of efficient conditional systems to abrogate proteins. We report the adaptation of a conditional technology, knocksideways (KS), for use in Plasmodium berghei, which can potentially rapidly inactivate proteins of interest through relocalisation. The system is induced using rapamycin, which allows for KS both in vitro and in vivo and is effective more rapidly than any other reported system. KS utilises pairs of fluorescent tags that facilitate live imaging and allows for rapid confirmation of efficient protein redistribution on live parasites, allowing for streamlined workflows. We demonstrate the characteristics of the system using transgenically expressed cytoplasmic GFP and provide proof of principle by inducibly redistributing a number of proteins with different native, subcellular locations.  We also demonstrate that KS can be applied to both mammalian and insect stages of Plasmodium. KS expands the range of (conditional) technologies for genetic manipulation of malaria parasites and offers the potential to be further developed for medium throughput phenotype screens.